2012
DOI: 10.1016/j.ccr.2012.08.010
|View full text |Cite
|
Sign up to set email alerts
|

STAT3-Driven Upregulation of TLR2 Promotes Gastric Tumorigenesis Independent of Tumor Inflammation

Abstract: Gastric cancer (GC) is associated with chronic inflammation; however, the molecular mechanisms promoting tumorigenesis remain ill defined. Using a GC mouse model driven by hyperactivation of the signal transducer and activator of transcription (STAT)3 oncogene, we show that STAT3 directly upregulates the epithelial expression of the inflammatory mediator Toll-like receptor (TLR)2 in gastric tumors. Genetic and therapeutic targeting of TLR2 inhibited gastric tumorigenesis, but not inflammation, characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
286
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(308 citation statements)
references
References 59 publications
17
286
3
2
Order By: Relevance
“…6E). We previously showed that TLR2/MyD88 signaling in tumor cells promotes gastric tumorigenesis in gp130 F/F mice (19,28). Consistent with these findings, it has been shown that TLR2 signaling in cancer cells plays a tumor-promoting role through the enhancement of stemness (23,24).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…6E). We previously showed that TLR2/MyD88 signaling in tumor cells promotes gastric tumorigenesis in gp130 F/F mice (19,28). Consistent with these findings, it has been shown that TLR2 signaling in cancer cells plays a tumor-promoting role through the enhancement of stemness (23,24).…”
Section: Discussionsupporting
confidence: 63%
“…F/F mice, in which hyperactivation of Stat3 promotes gastric tumorigenesis via the TLR2/MyD88 cascade (19,28,29). The expression levels of Tnf, Cd14, Casp1, Il1a, and Tlr2 were significantly increased in gp130 F/F tumors; however, this upregulation was not suppressed in the gp130 F/F Myd88 À/À mouse tumors, in which Myd88 was disrupted in both epithelial and stromal cells ( Supplementary Fig.…”
Section: The Suppression Of the Inflammatory Responses In Gan Myd88mentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, a number of pharmacological studies have demonstrated crocetin to have multiple activities, including anti-inflammatory (35,36) and anti-oxidant (37,38) effects. Therefore, it was hypothesized that the anti-oxidant and anti-inflammatory effects of crocetin may also be considered to be involved in several synergistic antitumor mechanisms (39,40). Further in vivo studies are required to investigate in greater detail the mechanisms and pharmacokinetics of crocetin and to provide an experimental basis for the clinical application of the drug.…”
Section: D a Bmentioning
confidence: 99%
“…10 Moreover, mutation in the IL-6 and IL-11 coreceptor, gp130, results in gastric tumor development through activation of Stat3. 11,12 On the other hand, the role of TNF-a in gastric tumorigenesis has not yet been investigated using a genetic mouse model.…”
Section: Introductionmentioning
confidence: 99%